2009
DOI: 10.1016/j.neuroscience.2009.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural relationship between N-methyl-d-aspartate-NR1 receptor subunit and mu-opioid receptor in the mouse central nucleus of the amygdala

Abstract: The central nucleus of the amygdala (CeA) is an important neuroanatomical substrate of emotional processes that are critically involved in addictive behaviors. Glutamate and opioid systems in the CeA play significant roles in neural plasticity and addictive processes, however the cellular sites of interaction between agonists of N-methyl-d-aspar-tate (NMDA) and μ-opioid receptors (μOR) in the CeA are unknown. Dual labeling immunocytochemistry was used to determine the ultrastructural relationship between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 68 publications
(85 reference statements)
7
34
0
Order By: Relevance
“…Techniques used to discern the cellular distribution of glutamate and opioid receptor/ligand constituents have provided critical information pertaining to functional implications of interactions between these systems (Glass, et al, 2009). Using immunohistochemistry combined with electron microscopy, such high-resolution neuroanatomical studies have revealed sites of receptor interaction that can inform experimental approaches using pharmacological manipulation to target these systems under conditions of chronic use of abused substances versus control conditions.…”
Section: Benefits Of a High Resolution Immuno-electron Microscopy Appmentioning
confidence: 99%
“…Techniques used to discern the cellular distribution of glutamate and opioid receptor/ligand constituents have provided critical information pertaining to functional implications of interactions between these systems (Glass, et al, 2009). Using immunohistochemistry combined with electron microscopy, such high-resolution neuroanatomical studies have revealed sites of receptor interaction that can inform experimental approaches using pharmacological manipulation to target these systems under conditions of chronic use of abused substances versus control conditions.…”
Section: Benefits Of a High Resolution Immuno-electron Microscopy Appmentioning
confidence: 99%
“…Importantly, these two receptors colocalize on single neurons within the CNS (reviewed by Trujillo, 2002), and at the ultrastructural level both receptors show convincing colocalization (Glass et al, 2009). Specifically, the midbrain periaqueductal gray (PAG) is densely innervated by glutamatergic projections from the forebrain, and there is robust MOR-NMDAR colocalization in the dendrites and somata of ventrolateral PAG neurons (Commons et al, 1999;Narita et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In one such midbrain structure, the periaqueductal gray matter (PAG), the MOR are located superficially in the ventrolateral PAG and thus, they are accessible from the CSF [21]. At the ultrastructural level, MOR and NMDAR co-localize convincingly [22]. Specifically, the mesencephalic PAG is densely innervated by glutamatergic projections from the forebrain and these receptors co-localize robustly in the dendrites and somata of ventrolateral PAG neurons [10,23].…”
Section: Introductionmentioning
confidence: 99%